Space jam [videorecording (DVD)] - Pytka, Joe; Jordan, Michael, 1963-; Knight, Wayne; Randle, Theresa, 1967-; Murray, Bill, 1950 September 21-; DeVito, Danny (Distributed by Warner Home Video, 2011)
Michael Jordan is "recruited" from his baseball team to help the Warner Bros. characters defeat a group of aliens in a basketball game where the stakes are their freedom for all time.